2002
DOI: 10.1038/sj.onc.1205633
|View full text |Cite
|
Sign up to set email alerts
|

Increased arylhydrocarbon receptor expression offers a potential therapeutic target for pancreatic cancer

Abstract: The arylhydrocarbon receptor (AhR) was initially identified as a member of the adaptive metabolic and toxic response pathway to polycyclic aromatic hydrocarbons and to halogenated dibenzo-p-dioxins and dibenzofurans. In the present study, we sought to determine the functional significance of the AhR pathway in pancreatic carcinogenesis. AhR expression was analysed by Northern blotting. The exact site of AhR expression was analysed by in situ hybridization and immunohistochemistry. The effects of TCDD and four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 80 publications
8
111
1
Order By: Relevance
“…These results are consistent with findings in mouse skin carcinogenesis assays that showed that TCDD pretreatment is anticarcinogenic under conditions of low doses of the tumor inducer DMBA [Lesca et al, 1994]. AHR is also expressed at high levels in pancreatic cancer tissues, and TCDD and other AHR agonists inhibit pancreatic cancer cell growth [Koliopanos et al, 2002].…”
Section: Cell Cycle Arrest Induced By Ahr Ligandssupporting
confidence: 80%
“…These results are consistent with findings in mouse skin carcinogenesis assays that showed that TCDD pretreatment is anticarcinogenic under conditions of low doses of the tumor inducer DMBA [Lesca et al, 1994]. AHR is also expressed at high levels in pancreatic cancer tissues, and TCDD and other AHR agonists inhibit pancreatic cancer cell growth [Koliopanos et al, 2002].…”
Section: Cell Cycle Arrest Induced By Ahr Ligandssupporting
confidence: 80%
“…A number of studies demonstrate AhR expression, usually at notably high levels, in rodent and human tumors (Ma and Whitlock, 1996;Weiss et al, 1996;Ge and Elferink, 1998;Puga et al, 2000Puga et al, , 2002Trombino et al, 2000;Safe, 2001;Koliopanos et al, 2002;Abdelrahim et al, 2003;Hayashibara et al, 2003;Zhang et al, 2003;Thomsen et al, 2004). Furthermore, we have shown in a primary mammary tumor model that much of that AhR resides in the tumor cell nucleus, a result suggestive of constitutive AhR activation in the absence of exogenous ligands (Wang et al, 1995;Trombino et al, 2000).…”
Section: Resultsmentioning
confidence: 69%
“…This question is all the more significant in light of several studies associating AhR activation with cell growth (Ma and Whitlock, 1996;Weiss et al, 1996;Ge and Elferink, 1998;Puga et al, 2000Puga et al, , 2002Abdelrahim et al, 2003;Ohtake et al, 2003;Thomsen et al, 2004) or apoptosis regulation (Yamaguchi et al, 1997;Matikainen et al, 2001Matikainen et al, , 2002Ryu et al, 2003;Caruso et al, 2004). Indeed, the demonstrable influence of the AhR on at least tumor cell growth has motivated the targeting of this receptor/ transcription factor or its gene targets for cancer therapy (Safe, 2001;Koliopanos et al, 2002;Abdelrahim et al, 2003;Maecker et al, 2003;Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chemoprotective natural products including flavonoids, indole-3-carbinol and related heteroaromatics, green tea components, and other polyhydroxy aromatic antioxidants also bind the AhR (Denison, Seidel, Rogers, Ziccardi, Winter, and Heath-Pagliuso, 1998;Denison and Nagy, 2003) and exhibit both AhR agonist and antagonist activities. Ligand-dependent activation of the AhR inhibits growth of ERpositive breast cancer cells , and growth inhibitory effects of AhR agonists have also been observed in pancreatic, prostate and ovarian cancer (Koliopanus et al, 2002;Morrow et al, 2004;Rowlands et al, 1993). These observations have led to development of selective AhR modulators (SAhRMs) as a potential new class of drugs for treatment of these cancers (McDougal, Wormke, Calvin, and Safe, 2001;Safe, McDougal, Gupta, and Ramamoorthy, 2001;Safe and Wormke, 2003).…”
Section: Discussionmentioning
confidence: 99%